The Effect of Financial Development on Energy Consumption: Evidence from Russia - Mukhtarov, Shahriyar; Karacan, Rıdvan; Aliyev, Fuzuli; Ismayilov, Vuqar (International Journal of Energy Economics and Policy, 2022)
This paper explores the effect of financial development, economic growth, and energy prices represented by consumer price index (CPI) on energy consumption in Russia by performing VECM, CCR, DOLS and FMOLS analyses to the annual data from 1995 to 2019. The findings of this empirical analysis reveal that financial development and economic growth have positive impact on energy consumption in Russia. Furthermore, the effects of energy prices expressed by CPI is revealed to be negative, which is consistent with the theory and expectations in practice. Based on the findings of this study, the nexus and impacts of financial development on energy consumption are discussed, as well as plausible explanations and policy implications.